2001
DOI: 10.1093/jn/131.10.2753
|View full text |Cite
|
Sign up to set email alerts
|

Life Span Is Prolonged in Food-Restricted Autoimmune-Prone (NZB × NZW)F(1) Mice Fed a Diet Enriched with (n-3) Fatty Acids

Abstract: Moderate food and/or energy (calorie) restriction delays age-related immune dysfunction and prolongs life span in multiple animal models. The amount and type of dietary fatty acids can also profoundly affect life span. Marine-derived fish oils contain (n-3) fatty acids, which have potent anti-inflammatory properties. We therefore examined the influence of food restriction (40% overall reduction in intake of all dietary components) combined with substitution of fish oil for corn oil in a factorial design. Autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 56 publications
5
51
0
2
Order By: Relevance
“…Although no previous studies of the effects of FO on lifespan of long‐lived strains of mice have been reported, several studies have been reported in which omega‐3 fatty acids increased lifespan in short‐lived autoimmune‐prone (NZB × NZW)F1 mice (Jolly et al ., 2001; Fernandes, 2008). A demographic analysis of the survival of fish oil‐fed (NZBxNZW)F(1) mice by de Magalhaes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although no previous studies of the effects of FO on lifespan of long‐lived strains of mice have been reported, several studies have been reported in which omega‐3 fatty acids increased lifespan in short‐lived autoimmune‐prone (NZB × NZW)F1 mice (Jolly et al ., 2001; Fernandes, 2008). A demographic analysis of the survival of fish oil‐fed (NZBxNZW)F(1) mice by de Magalhaes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, LC n-3 PUFA also decrease inflammation [14], including obesity-associated low-grade inflammation of WAT [15,16], characterised by altered secretion patterns of adipokines, which contributes to insulin resistance [1]. The anti-inflammatory effects of LC n-3 PUFA probably depend on the formation of their active metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al observed that the life span of mice fed a DHA-rich diet was longer than that of mice fed a lard diet abundant in saturated fatty acids and a safflower oil diet rich in linoleic acid (11), while Jolly et al reported that the life span of a mouse autoimmune model was prolonged in a group fed n-3 fatty acid-rich fish oil, compared to that in a group fed a corn diet (12). However, it has also been reported that the life spans of BHE/cdb rats (a rat non-obese NIDDM and hyperlipidemia model) and senescence-accelerated mice were shorter in animals fed an n-3 fatty acid-rich diet than in those fed a linoleic acid-rich safflower oil diet (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary lipid type-associated variations in the rat and mouse life span have been reported (11)(12)(13)(14)(15), suggesting that the dietary n-6/ n-3 ratio affects the life span of rats. However, the saturated : monounsaturated : polyunsaturated fatty acid ratio (S : M : P ratio) of test fats used in these experiments was not regulated, so it is not clear whether the influence on lifespan of the lipid type was caused by the n-6/ n-3 ratio.…”
mentioning
confidence: 99%